2021
DOI: 10.3390/su13020921
|View full text |Cite
|
Sign up to set email alerts
|

Housefly Maggot Meal as a Potent Bioresource for Fish Feed to Facilitate Early Gonadal Development in Clarias gariepinus (Burchell,1822)

Abstract: Food security is threatened by the global increase of human population, climate change, inequality of wealth distribution, the state of natural resources, peace and sustainability, among others. Aquaculture has become an important part of the food supply, hence contributing to food security. Sustainable fish production, which represents an important affordable protein supply, should therefore involve feed formulation and production techniques that are not dependent on fish meal as the protein source. It is on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Before such food samples are analyzed, sorting is a method to eliminate any visibly present soil, dust, and other physical pollutants. The average value of 15.8 g/100 g reported for fish [37] is lower than the ash content of termites, which is also lower. The carbohydrate content per 100 grams varies from 0.7 to 8.7 g. However, another study [39] recorded a value of up to 29.0 g/100 g. The range of dietary fiber per 100 grams is 6.2 to 7.2 g. Because chitin and cellulose have structural similarities, the fiber seen in insects is actually chitin [24].…”
Section: Proximate Compositionmentioning
confidence: 67%
See 2 more Smart Citations
“…Before such food samples are analyzed, sorting is a method to eliminate any visibly present soil, dust, and other physical pollutants. The average value of 15.8 g/100 g reported for fish [37] is lower than the ash content of termites, which is also lower. The carbohydrate content per 100 grams varies from 0.7 to 8.7 g. However, another study [39] recorded a value of up to 29.0 g/100 g. The range of dietary fiber per 100 grams is 6.2 to 7.2 g. Because chitin and cellulose have structural similarities, the fiber seen in insects is actually chitin [24].…”
Section: Proximate Compositionmentioning
confidence: 67%
“…Termites have excellent protein quality that is advantageous for human and animal nutrition [5], even though these values are lower than those recorded in fish (70.6 g/100 g) and soybean (51.8 g/100 g) [37]. As can be seen in Table 1, the termites' lipid content varied from 44.8 to 47.3 g/100 g. Another study [38] found 19.70-24.10 g/100 g for various termite species in Nigeria, while a previous study [35], also recorded 53.4 g/100 g for sun-dried termites.…”
Section: Proximate Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional profile of the larvae covers the amino acid requirements of many fish of commercial interest (Nogales-Mérida et al, 2018) and its application as ingredient for the aquaculture sector has given encouraging results. Many investigations have been conducted on freshwater aquacultured species such as the Nile tilapia (Ogunji et al, 2007;Ogunji et al, 2009;Ezewudo et al, 2015;Wang et al 2017;Alofa et al, 2020), different species of catfish (Sogbesan et al, 2006;Dong et al, 2013;Ipinmoroti et al, 2015;Ogunji et al, 2021, Fawole 2023), carp species (Ogunji et al, 2009,Dong et al, 2013 and rainbow trout (Oncorhynchus mykiss; Spinelli, 1980;St-Hilaire et al, 2007), as well as marine and brackish species (Ido et al, 2015;Lin & Mui, 2017;Panteli et al, 2021;Mastoraki et al, 2020).…”
Section: Livestock and Aquaculturementioning
confidence: 99%
“…Positive effects on growth were obtained at high inclusion rates (65 -75 % of total diet; Ipinmoroti et al, 2019;Ogunji et al, 2021). However, inclusions higher than 30% lowered growth performance in Nile tilapia (Aniebo et al, 2009;Fasakin et al, 2003).…”
Section: Livestock and Aquaculturementioning
confidence: 99%